2022
DOI: 10.1155/2022/2667415
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Carcinoma of the Breast Presenting as Gingival Swelling in the Maxilla: A Case Report

Abstract: Background. Metastatic cancers in the oral cavity are usually very rare and are usually an indication of widespread malignancy. In some cases, oral metastasis was found to be the first presentation of distant site tumours. Even though oral metastatic lesions may be found anywhere in the oral cavity, they commonly present in the posterior areas of the jaw bones. Among the soft tissues, the gingiva is the most common site. The presence of inflammation in the gingiva and the role of periodontal microbiota are sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Our research strategy revealed a total of 88 relevant papers 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90…”
Section: Resultsmentioning
confidence: 99%
“…Our research strategy revealed a total of 88 relevant papers 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90…”
Section: Resultsmentioning
confidence: 99%
“…Unconventional sites, such as the mandibular condyle or maxillary gingiva, can be colonized by the secondary spreading of primary cancer that can manifest with subtle or even without any symptoms [38][39][40].…”
Section: Discussionmentioning
confidence: 99%